Subsurface crack damage in silicon wafers induced by resin bonded diamond wire sawing. (January 2017) - Liu, Tengyun; Ge, Peiqi; Bi, Wenbo; Gao, Yufei
Abstract: In order to optimize the process of wire sawing, this work studied the subsurface crack damage in silicon wafers induced by resin bonded diamond wire sawing using theoretical and experimental methods. A novel mathematical relationship between subsurface crack damage depth and processing parameters was established according to the indentation fracture mechanics. Sawing experiment using resin bonded diamond wire saw was performed on a wire saw machine. The validity of the proposed model was conducted by comparing with the experimental results. At last, the influences of processing parameters on subsurface damage depth were discussed. Results indicate that the median cracks are mainly oblique cracks which generate the subsurface crack damage. On the diamond wire saw cross section, the abrasives with the position angle 78° between abrasive position and vertical direction generate the largest subsurface damage depth. Furthermore, abrasives, generating the subsurface damage, tend away from the bottom of diamond wire with the increase of wire speed or decreases with the increase of feed rate. However, the wire speed and feed rate have opposite effects on the subsurface crack damage depth. In addition, the subsurface crack damage depth is unchanged when the ratio of feed rate and wire speed does not change.